Therapeutic effect of Cnidium officinale Makino extract on ovariectomized hind-limb ischemic mice - Hyun Yang; Dong Ho Jung; Hye Won Lee (Integrative Medicine Research)
Background: Cnidium officinale Makino (COM) has been used traditionally to treat female menstrual disorders, such as amenorrhea, hypomenorrhea and oligomenorrhea, by improving blood circulation. The present study aimed to investigate the alleviating effect of COM extracts on surgical injuryinduced ischemia in the hind-limb of mice. Methods: In this study, female C57BL/6 mice were ovariectomized, and the vessels of the hind-limb were excised after ligation by surgical silk (6–0). The mice were orally administered with COM (150 or 300 mg/kg/day) for 3 weeks, and the blood flow rate of hind-limbs was evaluated by using a laser Doppler system after hind-limb ischemic surgery in an in vivo study. Additionally, the migration and tube formation of human umbilical vein endothelial cells (HUVECs) were evaluated in an in vitro study. Results: The blood flow rate was synchronized to the nonischemic lesion of the hind-limb, and its elevation compared to the vehicle was observed at 14 and 21 days after hind-limb ischemic surgery in COM-treated groups. The number of capillaries increase in a dose-dependent manner in the COM-treated groups (150 and 300 mg/kg). In HUVECs, the activities of cell migration were significantly increased by 50 and 75 μg/mL for the COM-treated groups. In addition, the number of tubule branches and junctions was also increased by doses of COM (50 and/or 75 μg/mL). Conclusion: The results of our study suggested that the COM extract may have therapeutic application for the treatment of hind-limb ischemic damage, which is due to the improvement of the peripheral angiogenetic system. Keywords: Cnidium officinale Makino, Hind-limb ischemia, Angiogenesis, Blood flow